Working Class Hero. - Grier, David Alan (Computer (00189162), 2007)
The article describes a programmer's quest for meaningful contributions to the common good, linking his personal values with open source software, Linux, and a long tradition in high technology of good deeds of mutual benefit. The author describes such efforts as the SHARE cooperative associated with IBM, established in 1955. Similar user groups followed. In time, computer manufacturers recognized the groups' interest in participating in product decisions. The role of user groups shifted away from common solidarity, as users began buying software rather than writing it themselves. The author concludes that independent programmers may still have an opportunity to contribute to the common good.